2020
DOI: 10.1101/2020.12.17.423264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clustered Loss of Dendritic Spines Characterizes Encoding of Related Memory

Abstract: Generation of new spines is often thought of as a correlate of memory and loss of spines is considered representing memory loss. Contrary to common belief, we observe that spine loss has functional value in distinctly encoding related life events rather than causing memory loss. Using spatial autocorrelation of dendritic morphology obtained from in vivo longitudinal imaging, we show that clustered loss, rather than gain, of new spines characterizes the formation of related memory. This spatially selective dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The argument for the involvement of heterosynaptic plasticity in synaptic remodeling has been strengthened in vivo by the advance of longitudinal two-photon imaging of dendritic spines. Numerous studies performed over development and learning have shown that the rate of dendritic spine turnover and formation is strongly dependent on experience (Trachtenberg et al, 2002 ; Holtmaat et al, 2005 ; Zuo et al, 2005a , b ; Hofer et al, 2009 ; Xu et al, 2009 ; Chen et al, 2012 ; Fu et al, 2012 ; Lai et al, 2012 ; van Versendaal et al, 2012 ; Yang et al, 2014 , 2016 ; Miquelajauregui et al, 2015 ; Barnes et al, 2017 ; El-Boustani et al, 2018 ; Frank et al, 2018 ; Jungenitz et al, 2018 ; Kumar et al, 2020 ). The experience-dependence of synaptic dynamics is consistent across different brain areas and occurs for both excitatory and inhibitory synapses.…”
Section: In Vivo Plasticity-mediated Synaptic Reorganization On Dendritesmentioning
confidence: 99%
See 1 more Smart Citation
“…The argument for the involvement of heterosynaptic plasticity in synaptic remodeling has been strengthened in vivo by the advance of longitudinal two-photon imaging of dendritic spines. Numerous studies performed over development and learning have shown that the rate of dendritic spine turnover and formation is strongly dependent on experience (Trachtenberg et al, 2002 ; Holtmaat et al, 2005 ; Zuo et al, 2005a , b ; Hofer et al, 2009 ; Xu et al, 2009 ; Chen et al, 2012 ; Fu et al, 2012 ; Lai et al, 2012 ; van Versendaal et al, 2012 ; Yang et al, 2014 , 2016 ; Miquelajauregui et al, 2015 ; Barnes et al, 2017 ; El-Boustani et al, 2018 ; Frank et al, 2018 ; Jungenitz et al, 2018 ; Kumar et al, 2020 ). The experience-dependence of synaptic dynamics is consistent across different brain areas and occurs for both excitatory and inhibitory synapses.…”
Section: In Vivo Plasticity-mediated Synaptic Reorganization On Dendritesmentioning
confidence: 99%
“…Novel experiences can promote clustered spine formation (Fu et al, 2012 ; Yang et al, 2014 , 2016 ; Frank et al, 2018 ; Kumar et al, 2020 ), and clustered spine elimination can also occur in response to learning, as well as during sensory enrichment and deprivation (Chen et al, 2012 ; Lai et al, 2012 ; Frank et al, 2018 ; Kumar et al, 2020 ). Some studies have found that clustered spine elimination is related to encoding specific information such as familiar memories (Kumar et al, 2020 ) or fear conditioning (Lai et al, 2012 ). Frank et al ( 2018 ) have suggested that experience-dependent spine elimination could facilitate clustered spine formation during learning.…”
Section: In Vivo Plasticity-mediated Synaptic Reorganization On Dendritesmentioning
confidence: 99%